Effective English Language Teacher: A Comparison of Perceptions of Pakistani College Teachers and Students - Mahboob Ali Naper,; Muhammad Younus,; Jibran Khan, (Dialogue Social Science Review (DSSR), 2025)
This study examined the perceptions of college teachers and students about effective English language teacher in Sindh, Pakistan. Using a quantitative research design, data were collected from 80 English language teachers and 300 students through a structured questionnaire comprising 50 items. Independent samples t-tests were conducted to compare responses between the two groups. Results revealed significant perceptual differences across most items, with teachers consistently assigning higher importance to attributes such as lesson planning, grading based on group tasks and student ability, use of English-only instruction, discipline, and teacher professionalism. In contrast, students rated these characteristics lower, suggesting a misalignment in expectations. Moreover, differences were found in perceptions of public college teachers with their students and rural college teachers and their students. Contrary to this, private college teachers and urban college teachers did not show significant differences with their students. These findings underscore the need for greater teacher-student dialogue, inclusive curriculum planning, and pedagogical transparency particularly in public colleges and in rural areas. The study concludes that bridging this perceptual gap is essential for enhancing instructional effectiveness and student engagement. Limitations include its geographic focus on Sindh and reliance on quantitative methods. Future research should incorporate qualitative approaches and broader sampling to gain deeper insights into contextual factors influencing these perceptions. Keywords: Perceptions, Effective English Teacher, Students, Colleges